The Perspectives of the Academic Staff and Students of the American University of Madaba (AUM) on Cyber-Truancy during Covid-19 Pandemic: Challenges and Solutions - Madanat , Hanan; Tarawneh, Majid (Dirasat: Human and Social Sciences, 2023)
Objectives: This paper examines the perspectives of academic staff and students at the American University of Madaba (AUM) on cyber-truancy during the COVID-19 pandemic, addressing challenges and proposing solutions to enhance student engagement in online learning. Methods: Case-study methodology requires detailed investigation of a situation. To attain the required information, two methods of data collection were utilized, namely, a structured (Likert scale) questionnaire and an interview distributed to a representative sample of AUM’s academic staff and students. The data was analyzed by using SPSS. Results: The study found the following results. First, all respondents show a high level of awareness of the cyber-truancy. Second, technological and behavioral factors contribute to increasing truancy rates among students. Third, the novelty of the experience as well as enforcing strict policies are crucial challenges that hinder online learning. Conclusions: The paper concludes with suggested solutions, which include enforcing strict policies to curb cyber-truancy, enhancing parental control, and spreading awareness among students regarding the detrimental effects of cyber-truancy.